PENGARUH KONDISI EKONOMI DAN KINERJA KEUANGAN TERHADAP RETURN SAHAM PERUSAHAAN FOOD AND BEVERAGES DI BURSA EFEK INDONESIA - Putra, I Wayan Krisna; Dana, I Made (E-Jurnal Manajemen, 2014)
The purpose of this study was to determine the effect of the inflation rate, gross domestic product (GDP), debt to equity ratio (DER), return on assets (ROA), market to book value (MBV) towards the stock returns  on the food and beverages company in Indonesia Stock  Exchange (IDX) 2010-2013. Data collection methods used in this study is a nonparticipant observation method. The population used is the company that is categorized into food and beverages sector in Indonesia Stock Exchange in 2010 - 2013, the sampling method used in this study is purposive sampling. The data analysis technique used is the Multiple Linear Regression. The results showed that the market to book value is partially positive and significant effect on stock returns, while the rate of inflation, gross domestic product, the debt to equity ratio, return on assets insignificant effect on stock returns food and beverages company in Indonesia Stock Exchange from 2010 -2013.
Keywords: return saham; analisis fundamental